Replication protein RPA2A regulates floral transition by cooperating with PRC2 in Arabidopsis. Issue 6 (29th June 2022) - Zhang, Xiaoling; Li, Wenjuan; Liu, Yue; Li, Yanzhuo; Li, Yang; Yang, Wandong; Chen, Xiangsong; Pi, Limin; Yang, Hongchun
Summary: RPA2A is a subunit of the conserved heterotrimeric replication protein A (RPA) in Arabidopsis, which is an essential replisome component that binds to single‐stranded DNA during DNA replication. RPA2A controls a set of developmental processes, but the underlying mechanism is largely unknown. Here we show that RPA2A represses key flowering genes including FLOWERING LOCUS T ( FT ), AGAMOUS ( AG ) and AGAMOUS LIKE 71 ( AGL71 ) to suppress floral transition by cooperating with the PRC2 complex. RPA2A is vigorously expressed in dividing cells and required for correct DNA replication. Mutation of RPA2A leads to early flowering, which is dependent on ectopic expression of key flowering genes including FT molecularly and genetically. RPA2A and PRC2 have common target genes including FT, AG and AGL71 supported using genetic analysis, transcriptome profiling and H3K27me3 ChIP‐seq analysis. Furthermore, RPA2A physically interacts with PRC2 components CLF, EMF2 and MSI1, which recruits CLF to the chromatin loci of FT, AG and AGL71 . Together, our results show that the replication protein RPA2A recruits PRC2 to key flowering genes through physical protein interaction, thereby repressing the expression of these genes to suppress floral transition in Arabidopsis.